Biological knowledge discovery handbook : preprocessing, mining and postprocessing of biological data - Elloumi, Mourad; Zomaya, Albert Y. (Wiley, 2014)
The first comprehensive overview of preprocessing, mining, and postprocessing of biological data Molecular biology is undergoing exponential growth in both the volume and complexity of biological data-and knowledge discovery offers the capacity to automate complex search and data analysis tasks. This book presents a vast overview of the most recent developments on techniques and approaches in the field of biological knowledge discovery and data mining (KDD)-providing in-depth fundamental and technical field information on the most important topics encountered.